2005
DOI: 10.1007/s10482-004-2346-4
|View full text |Cite
|
Sign up to set email alerts
|

The curdlan-type exopolysaccharide produced by Cellulomonas flavigena KU forms part of an extracellular glycocalyx involved in cellulose degradation

Abstract: The genus Cellulomonas is comprised of a group of Gram-positive, soil bacteria capable of utilizing cellulose as their sole source of carbon and energy. Cellulomonas flavigena KU was originally isolated from leaf litter and subsequently shown to produce large quantities of a curdlan-type (beta-1,3-glucan) exopolysaccharide (EPS) when provided with an excess of glucose or other soluble carbon-source. We report here that curdlan EPS is also produced by Cellulomonas flavigena KU when growing on microcrystalline c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 30 publications
2
31
1
Order By: Relevance
“…It is clear that there are numerous strategies for effective surface attachment, including extracellular polymer production and carbohydrate-binding modules present as part of both cellulosomes and individual cell surface-associated enzymes (Dumitrache et al, 2013a;Kenyon et al, 2005). Such mechanisms demonstrate how surface attachment provides a competitive strategy to acquire substrate where proximity facilitates efficient cellulose hydrolysis and assimilation.…”
Section: Discussionmentioning
confidence: 99%
“…It is clear that there are numerous strategies for effective surface attachment, including extracellular polymer production and carbohydrate-binding modules present as part of both cellulosomes and individual cell surface-associated enzymes (Dumitrache et al, 2013a;Kenyon et al, 2005). Such mechanisms demonstrate how surface attachment provides a competitive strategy to acquire substrate where proximity facilitates efficient cellulose hydrolysis and assimilation.…”
Section: Discussionmentioning
confidence: 99%
“…Kenyon and Buller (20) demonstrated that the aerobic gram-positive cellulolytic bacterium Cellulomonas flavigena KU produces curdlan, a ␤-1,3-glucan, and that this polymer is a component of the extracellular polymeric matrix of the bacterium during growth on cellulose. Interestingly, C. flavigena produces considerably more curdlan when grown on cellobiose (19), under which conditions the organism grows in a purely planktonic mode and would appear to have little need for an EPS that adheres to cellulose, unless its synthesis was a specific strategy for binding to newly encountered cellulose. By contrast, Mosoni and Gaillard-Martinie (33) reported that R. albus 20 forms only a very thin and irregular glycocalyx during growth on cellobiose.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the curdlan EPS produced by C. flavigena KU remains completely cell-associated, and no other EPSs have been detected Kenyon and Buller 2002). Kenyon et al (2005) provided evidence that the curdlan EPS produced by C. flavigena KU may form the basis of an extracellular biofilm matrix involved in cellulose degradation. In addition, there was already substantial proof that extracellular curdlan can serve as a source of carbon and energy for C. flavigena KU , whereas the curdlan produced by other strains of bacteria does (Nakanishi et al 1974).…”
Section: Discussionmentioning
confidence: 99%
“…Studies by Voepel and Buller (1990) clearly demonstrated that the curdlan EPS can be catabolized by C. flavigena KU if no other source of carbon and energy is available, and therefore, appears to function as an extracellular reserve compound. More recent studies have demonstrated that curdlan EPS is produced during growth of C. flavigena KU on a variety of substrates including cellulose and that the EPS forms the basis of an extracellular matrix promoting biofilm formation (Kenyon et al 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation